Fatty acid composition and organoleptic quality of four clones of durian (Durio zibethinus, murr.) - Berry, Shiv K. (Wiley, 1981)
This study was undertaken to determine and relate the lipid content and fatty acid composition of four different durian (Durio zibethinus, Murr.) clones, i.e., D24, D2, D66 and D8, with their respective organoleptic scores. Both lipid content and the fatty acid composition were found to vary among these clones. Clones D24 and D2, which contained a higher proportion of lipids but lower unsaturated fatty acid contents, received high organoleptic scores when compared to clones D66 and D8. It was found that the lower the palmitic: palmitoleic acid ratio in the lipid of a durian clone, the higher its organoleptic quality.